The orobasal organ (of Ackerknecht) is present in prenatal mice - Schumann, Sven; Munk, Jan R.; Schmeisser, Michael J.; Staeber, Moritz (Frontiers in Cell and Developmental Biology, 2025)
BackgroundIn 1912, the veterinary anatomist Eberhard Ackerknecht described morphologically highly variable epithelial invaginations behind the medial mandibular incisors. This orobasal organ (of Ackerknecht) is present in different mammalian species including humans, but its presence in mice was under debate in literature. While the function of the orobasal organ is still unknown, it might play a role in the development of cysts of the oral floor.MethodsH&E-stained histological serial slides of the developing oral floor of C57BL/6J mice embryos were investigated (n = 40).ResultsThe orobasal organ was present in mice and developed between prenatal days E15 and E17 (prevalence in E15 embryos: 0%, prevalence in E17 embryos: 90.5%). The organ was present both in male and female embryos. In E17, the organ had an average size of 68.75 (±41.1) μm x 58.75 (±8.5) μm x 345 (±28.3) μm (length x depth x width).DiscussionWhile the existence of an orobasal organ was already shown for pre- and postnatal rats, there was only one publication dealing with the orobasal organ in mice. In this study, adult mice were investigated and no orobasal organ was found. Here, we demonstrate the existence of an orobasal organ in mice, at least in embryos. The presence of the orobasal organ in a common model organism will help to investigate its pre- and postnatal development, as well as possible physiological functions of this structure.